Evaluation of Iraqi English for Specific Purposes (ESP) Curriculum Program (Journal of the College of Basic Education, 2022)
The research aims at formative evaluation to determine the quality and effectiveness of the English Language Curriculum Program for Specific Purposes in one of the departments of Ibn Rushd College of the University of Baghdad, which is mainly concerned with teaching education and psychology based on educational objectives. That is, to apply psychological principles and outcomes in education. The purpose of this assessment is to demonstrate the effectiveness of the current ESP curricular program titled "The Third Skill of Kubaisi 1989". It includes determining the effectiveness and quality of the ESP co-curricular program and how it can be improved based on students' needs. English for Specific Purposes (ESP) is "an approach to language teaching in which all decisions about content and method are based on why the learner is learning." (Hutchinson and Waters, 1993: 19. It is a type of curriculum in which the focus is on communication processes rather than structural, functional or theoretical elements, and content and goals are set on the specific needs of a particular group of learners (adapted and modified from Nunan, 1988). :158 and Richards and Schmidt, 2002:181) The proposed approach is a combination of communicative language teaching and the Hutchinson-Watters-based model of learning 1987. The following steps will be followed in order to achieve the objectives of the study: A quantitative method will be used (experimental approach / two groups - treatment and control) ), and a questionnaire will be distributed to both teachers and students to these colleges, designing an Iraqi ESP curriculum program in colleges of education, applying a proposed curriculum to a sample of Iraqi ESP students in colleges of education, and evaluating the proposed curriculum according to students’ achievements, behavior, and the views of specialists in it. .